2008
DOI: 10.1016/j.freeradbiomed.2008.01.015
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid induces manganese superoxide dismutase in human neuroblastoma through NF-κB

Abstract: Retinoids are signaling molecules that are involved in proliferation, differentiation and apoptosis during development. Retinoids exert their effects, in part, by binding to nuclear receptors, thereby altering gene expression. Clinical use of retinoids in the treatment of neuroblastoma is of interest due to their success in management of acute promyelocytic leukemia. Using the SK-N-SH human neuroblastoma cell line we investigated the effect of the differentiation agent, all-trans-retinoic acid (ATRA) on mangan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
6
38
0
1
Order By: Relevance
“…One of the ATRA-mediated signaling pathways is the activation of the transcription factor, NF-κB. [29][30][31] Consistent with these reports, the NF-κB repressor protein, inhibitor of NF-κB (IκB-α), level was decreased during ATRA-induced neuroblastoma treatment, and returned to normal levels when ATRA was replaced with DMSO ( Figure 2c). This observation was supported by NF-κΒ luciferase assay, where an increase in κB promoter activity upon ATRA treatment compared with DMSO-treated cells was observed (Figure 2d).…”
Section: Cyld Expression Is Associated With Clinical Outcomes In Neursupporting
confidence: 80%
“…One of the ATRA-mediated signaling pathways is the activation of the transcription factor, NF-κB. [29][30][31] Consistent with these reports, the NF-κB repressor protein, inhibitor of NF-κB (IκB-α), level was decreased during ATRA-induced neuroblastoma treatment, and returned to normal levels when ATRA was replaced with DMSO ( Figure 2c). This observation was supported by NF-κΒ luciferase assay, where an increase in κB promoter activity upon ATRA treatment compared with DMSO-treated cells was observed (Figure 2d).…”
Section: Cyld Expression Is Associated With Clinical Outcomes In Neursupporting
confidence: 80%
“…Activated Akt functions upstream of the overexpression of both Hsp70 and MnSOD chronic/repetitive heat stress catalase upregulation is not observed (data not shown) indicating perhaps the predominant generation of reactive oxygen species other than H 2 O 2 . Recent studies (Kiningham et al 2008;Shilo et al 2008) have demonstrated that MnSOD expression may be controlled by a number of transcription factors. The elements which control the transcription of MnSOD in heat-shocked cells and are downstream from Akt activation by heat shock remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…31 All-trans retinoic acid has been shown to induce differentiation in neuroblastoma cells through the activation of NFjB, which in turn induces MnSOD expression. 32 MnSOD expression has also been associated to the developing rat brain and liver. 33 However, those studies only show a temporal relationship between differentiation and MnSOD upregulation, demonstrating that this is an early event in the cell differentiation process.…”
Section: Discussionmentioning
confidence: 99%